2021
DOI: 10.35946/arcr.v41.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Family in Alcohol Use Disorder Recovery for Adults

Abstract: Alcohol use disorder (AUD) and family functioning are inextricably bound, and families are impacted negatively by AUD, but families show substantial improvements with AUD recovery. Family members can successfully motivate a person with AUD to initiate changes in drinking or to seek AUD treatment. During recovery, family members can provide active support for recovery. Several couple- or family-involved treatments for AUD have been developed and tested in rigorous efficacy trials. Efficacious treatments based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 91 publications
1
33
0
7
Order By: Relevance
“…Once drunk husbands were not in their senses and displaced their anger on wife and children. Extracts showed that women experienced physical discomfort like "… pain in the hands and feet (P1, 3,4,9,10), suffering, unable to perform daily activities "I cannot walk longer" (P1,4), "….fights and arguments till late at night (P2, 3,4), "…felt giddiness, sickly…" (P3), ".. tired (P2,8,9), weakness (P9)", "…I had headaches (P7), my health goes bad" (P2,7,8), felt anxiety, "I am tensed (P7,10), cannot even eat food (P3,7,8,9) … my weight has reduced (P2)…". These symptoms were clustered into the code physical symptoms and poor health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once drunk husbands were not in their senses and displaced their anger on wife and children. Extracts showed that women experienced physical discomfort like "… pain in the hands and feet (P1, 3,4,9,10), suffering, unable to perform daily activities "I cannot walk longer" (P1,4), "….fights and arguments till late at night (P2, 3,4), "…felt giddiness, sickly…" (P3), ".. tired (P2,8,9), weakness (P9)", "…I had headaches (P7), my health goes bad" (P2,7,8), felt anxiety, "I am tensed (P7,10), cannot even eat food (P3,7,8,9) … my weight has reduced (P2)…". These symptoms were clustered into the code physical symptoms and poor health.…”
Section: Resultsmentioning
confidence: 99%
“…Rightly so, as it is not only the men who consume alcohol who bears the brunt of the disorder but the entire family, especially women in these families. [3][4][5] Besides, owing to the deeply entrenched patriarchal norms and traditions, most women in India do not enjoy their rights and opportunities fully. A culture of male dominance that values women as subordinate has been in practice for generations, and thus gender discrimination is deep-rooted in the fabric of Indian society.…”
mentioning
confidence: 99%
“…Все це глибоко травмує психіку дитини. Діти батьків, що зловживають алкоголем, вимушені пристосовуватися до умов постійного емоційного стресу [22][23][24].…”
Section: в н кузьмінов т в ткаченко р в лакинський вплив зловживання ...unclassified
“…Brewers prepare traditional alcoholic beverages for market, weddings, ceremonies, and other celebrations and to generate income for their daily needs. Some households generate enough income from the sale of these beverages to pay for their children's education, put food on the table and meet all the family’s basic needs [ 15 – 17 ]. There has been growing concerns about the hygienic handling of raw materials, production procedures and qualities of the final products including the rise in alcoholism, regarding home brewed alcoholic beverages in African [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%